Correlation Study between Debt-Equity Ratio and Asset Returns with Relative Market Value to Book Value in the Indonesian Mining Industry (2020-2022) - Rahman, Moch Ridho Ghazali (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
This research aims to analyze the influence of Debt to Equity Ratio and Return on Asset on Price to Book Value within the Indonesian mining industry for the years 2020-2022. Utilizing a quantitative methodology and an associative approach, the study was carried out from April to June 2023. From a population of 80 mining companies listed on the Indonesia Stock Exchange, 25 were selected as samples through purposive sampling Findings suggest that the Debt to Equity Ratio does not significantly impact Price to Book Value. However, Return on Asset has a notable influence. Additionally, both variables collectively have an effect on Price to Book Value.